Examining the Use of Organizational Commitment and Total Quality Management to Enhance University Performance - Hamzah, A Hadian Pratama; Nurhasanah, Nurhasanah; Saleha, Eha (Journal of Social Work and Science Education, 2025)
The output of this study is to develop a TQM implementation strategy to improve the inclusive performance of employees within the Universitas Terbuka (UT) environment. This research design leads to a mixed method in combining quantitative and descriptive data in analyzing the conditions of field findings. Quantitative descriptive research comprises problem formulation, model preparation, data collection, analysis, and application. Interpretative Structural Modeling (ISM) is the analytical technique employed in this study. Bhattacharya and Momaya’s application of ISM (2009), is a design that involves many relationships and interactions using tools and methods that allow a team of individuals to create a structure that outlines the connections between components in a single unit. The outcomes of classifying strategic components to enhance staff proficiency and knowledge in assisting UT’s as a PTN-BH consist of 15 criteria, which produce eight policy levels. Elements of stricter selection policies in recruiting. At the first level are the educational personnel (A1) and the components of mentoring in enhancing competence (A3). Four (four) sectors can be used to categorize the policy components that UT workers need to develop their skills and competences. Sector III (Linkages) is the most frequently utilized sector. This sector’s components are heavily reliant on one another, yet they also have a strong driving force.